The effects of Fama-French five factor and momentum factor on Islamic stock portfolio excess return listed in ISSI - U’um Munawaroh; Sunarsih Sunarsih (Faculty of Economics, Universitas Islam Indonesia, 2020)
Purpose – The purpose of this study is to examine the effect of Fama-French five-factor and momentum factor on Islamic stock portfolio excess returns listed in the Indonesia Sharia Stock Index (ISSI).Methodology – This study used return data from ISSI group, starting from January 2013 to December 2017, which are then formed into time series data with excess monthly stock portfolio. This study adapted the Fama and French (2015) methodology using 2x3 and 2x2 to form the portfolio and applied Ordinary Least Square (OLS) with monthly data frequency to test the relevance of the model to the expected stock return of 183 companies.Findings – The results showed that the risk premium, the book-to-market ratio which is proxied by High Minus Low (HML), the investment that is proxied by Conservative Minus Aggressive (CMA), and the momentum which is proxied by Up Minus Down (UMD) has a positive effect on the excess return of the company's stock portfolio registered in Indonesia Sharia Stock Index (ISSI) during the period. While, the size and profitability variable do not affect the expected stock return.Research limitations – The results of this study provides relevant information about the relationship between risk and stock return using Fama and French five-factor model and momentum. However, future researchers can expand the scale of the research by adding research periods and using daily return research data. It is intended that the results are more representative of the actual market conditions at the moment.Originality – Researches on the factors that influence the selection of Islamic stock portfolios based on excess return using Fama-French five-factor including the momentum factor are still limited. This study contributes to the asset pricing development by investigating factors influencing performance of ISSI’s portfolio excess return using five-factor model and momentum factor.